Legal Concepts of Subjective Right - Arriagada, María Beatriz (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
The aim of this paper is to identify and briefly characterize the basic or elementary concepts of subjective right and some of its possible combinations, on the understanding that such concepts or its combinations are always involved in the various uses of the term "subjective right" in legal discourse. To achieve this goal, the work is divided into four sections. The first section provides that a legal concept of rights is defined by its legal basis, and it must be distinguished from extra-legal grounds that justify or can justify the granting by law. In the second section, I analize Hohfeld’s explanatory model of subjective legal positions that serves as the basis for the identification and characterization of the legal concepts of subjective right that is performed in the third section. The fourth section presents some final considerations.doi: http://dx.doi.org/10.20318/eunomia.2016.3285
Keywords: Subjective right; rights; subjective legal positions; Hohfeld; regulative norms; competence norms; correlative duties; legal power